Two Weeks of “COVID-19” Search on PubMed.gov - Liu, Antonio (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: Letter to Editor, report the amount of literature generated over two weeks on PubMed.gov related to COVID-19 Methods: reporting the daily number of “hits” from “COVID-19” search on PubMed.gov Results: There were 66988 entries on PubMed.gov on the search word “COVID-19” on October 24, 2020. The average daily increase in number of entries was 335. Conclusions: point out the fact that the literature volume is increasing in an exponential manner (www.actabiomedica.it)